Local citizenship in a global age / Kenneth A. Stahl. - Stahl, Kenneth A., 1974- (Cambridge University Press, 2020)
Although it is usually assumed that only the federal government can confer citizenship, localities often give residents who are noncitizens at the federal level the benefits of local citizenship: access to medical care, education, housing, security, labor and consumer markets, and even voting rights. In this work, Kenneth A. Stahl demonstrates that while the existence of these 'noncitizen citizens' has helped to reconcile competing commitments within liberal democracy to equality and community, the advance of globalization and the rise of nationalist political leaders like Donald Trump has caused local and federal citizenship to clash. For nationalists, localities' flexible approach to citizenship is a Trojan horse undermining state sovereignty from within, while liberals see local citizenship as the antidote to a reactionary ethnic nationalism. This book should be read by anyone who wants to understand why citizenship has become one of the most important issues in national politics today.